Tracking Performance Of NPID Controller For Cutting Force Disturbance Of Ball Screw Drive - Abdullah, Lokman; Anang, Nur Amira; Jamaludin, Zamberi; Chiew, Tsung Heng; Maharof, Madihah; Retas, Zain; Che Ku Junoh, Sahida; Syed Salim, Syed Najib (Universiti Pahang Malaysia, 2017)
The high demand in tracking performance is crucial in machine tools application. Therefore,the purpose of this paper is to design a Nonlinear PID (NPID) controller for improvement of tracking performance via cutting force.The method was then compared with another method which was conventional PID controller. The configuration included different cutting force disturbances of 1500rpm, 2500rpm and 3500rpm. The parameters were set to 0.4Hz and 0.7Hz frequency for every 10mm and 20mm of amplitude, respectively.The investigation was centred on a comparative study of these two techniques which focused on x-axis of Googol Tech XY ball screw drive system. Results between the designed controllers were validated based on two types of errors; the maximum tracking error and root mean square error. Results showed that the NPID controller recorded better tracking performance compared to PID controller with an error reduction of about 33%. In addition,the results proved that NPID controller is highly practical and suitable to be used for ball screw drive. The controller can be further improved with the implementation of observer such as disturbance observer to compensate the cutting forces.